Practical report of Human Resource Unit / Mohd Faidzul Firdaus Sukaimi - Sukaimi, Mohd Faidzul Firdaus (University Technology MARA Sarawak, 2015)
Previously in the State Civil Service (SCS) it was divided into two parts, which are the Secretariat and the Divisional, in the year 1937, the Secretariat were the center of administration which lead by two Europeans officers and assisted by a Malay clerk, three Chinese descendent clerks and three office assistants. During the formation of Malaysia, there were about 2599 employees and the numbers increases up to 14208 employees in the year 2012. In the year 1966, the original Secretariat Office was moved to the Secretariat’s Building which is located in front of the Padang Sentral in Kuching from the Residence and Divisional Office right now As time goes by, the Secretariat was changed to State Employment Office in the year of 1976 then was again moved to Wisma Bapa Malaysia. Following based on the restructuring ofthe Government’s State Secretary ’s Office on the 1st of November 1995, the State Employment Office was known as the Human Resource Department A director was appointed to lead the organization and is responsible to the Deputy Secretary of the State Government (Human Resource). On the 25th of August 2001, the department was known as the Human Resource Unit as a result of the organizational restructuring of the Office of the Chief Minister. The current Human Resource Department Unit is divided into 4 Divisions and each division consist of different sections. The first division is the Policy and HR Communication Division that consist of the System and Database section, HR Communication Section, HR Transformation and Innovation Section. The next division is the Empioyee Assistance Division that consists of four sections namely. Recruitment Section, Career Development Section, Privileges and Development Section and Training and Development Section. The Human Resource Unit is still undergoing the HR Transformation that has a fresh mission, vision and motto. The continuous development and constant update will ensure the system is effective and efficient.